Investasi Saham Oleh Gen Z: Cerdas Finansial di Era Digital - Tiffany Candra; Andrew Darren; Maria Lusiana Kirani Adi Ningrat; Tan Ming Kuang (Politeknik Ganesha Medan, 2025)
This study examines how Gen Z stock investment decisions in the contemporary digital era are influenced by digital literacy, social media, and financial literacy. This tsudy intends to investigate the degree to which social media and financial literacy impact investment choices and pinpoint the function of digital literacy as a moderating factor that can bolster the association. This study’s quantitative methodology included the distribution of questionnaires to 327 Gen Z students from one of Bandung’s private universities. Purposive sampling was the method employed to make sure the sample was pertinent to the specified study goals. The Partial Least Square-Structural Equation Modelling (PLS-SEM) method was used to analyze the investment decisions, social media, digital literacy, and financial literacy variables that were measured using a Likert scale. The study’s findings suggest that social media and financial literacy positively influence investment choices, but digital literacy as a moderating factor cannot enchance the impact of social media and financial literacy on investment choices.